Respuesta :

I'll do the 2d problem to show you how it's done; always remember your order of operations - PEMDAS (Parenthesis, Exponents, Multiplication/Division, Addition/Subtraction).

6h - (9 - 3h) = 6 - 3(h + 2)    Distribute what's in front of the parenthesis to the inside

6h - 9 + 3h = 6 - 3h - 6        combine like-terms on both sides
9h - 9 = - 3h                        Isolate the variable onto one side
12h = 9                               Divide by 12 to get the variable alone
h = 9/12
ACCESS MORE